Security beyond the state : private security in international politics - Abrahamsen, Rita, 1966-; Williams, Michael C. (Michael Charles), 1960- (Cambridge, UK ; New York : Cambridge University Press, 2011)
"Across the globe, from mega-cities to isolated resource enclaves, the provision and governance of security takes place within assemblages that are de-territorialized in terms of actors, technologies, norms and discourses. They are embedded in a complex transnational architecture, defying conventional distinctions between public and private, global and local. Drawing on theories of globalization and late modernity, along with insights from criminology, political science and sociology, Security beyond the State maps the emergence of the global private security sector and develops a novel analytical framework for understanding these global security assemblages. Through in-depth examinations of four African countries - Kenya, Nigeria, Sierra Leone and South Africa - it demonstrates how global security assemblages effect the distribution of social power, the dynamics of state stability, and the operations of the international political economy, with significant implications for who gets secured and how in a global era"--Provided by publisher.
The untold story: the globalization of private security -- Late modernity and the rise of private security -- Power and governance: global assemblages and the security field -- Of oil and diamonds: global security assemblages in resource extraction -- Safer cities or cities of walls?: the politics of urban global security assemblages -- Security, politics, and global assemblages.
Includes bibliographical references (p. 238-267) and index.
Keywords: Security, International; Private security services